A case of donepezil-related torsades de pointes. (5th October 2015) - Kitt, Jamie; Irons, Robert; Al-Obaidi, Mohamed; Missouris, Constantinos
Abstract : An 80-year-old woman with Alzheimer's dementia presented with diarrhoea, vomiting and worsening confusion following an increase in donepezil dose from 5 to 10 mg. The ECG revealed prolongation of QTc interval. Soon after admission, she became unresponsive with polymorphic ventricular tachycardia (VT). Cardiopulmonary resuscitation with a 200 J shock was successful in establishing cardiac output. Following the discontinuation of donepezil, the QTc interval normalised and no further arrhythmias were recorded. Treatment with anticholinesterase inhibitors may result in life-threatening VT. Vigilance is required for the identification of this condition in patients presenting with presyncope, syncope or seizures.